Journal Editors and "Results-Free" Research: A Cautionary Note. (November 2016) - Ansell, Ben; Samuels, David
Should journals review submissions based only on the research question and research design, independent of whether the results are statistically and substantively significant? This special issue is the first effort in political science (and perhaps across the social sciences) to publish articles based on submission of research designs alone. We offer our thoughts on the process.